Educational Broadcast Programs Tuned In: Tool for Enhancing Learning in Educational Broadcasting to Residents of Canipaan, Leyte, Philippines - Ugsad, Rothelia Maria; Entoma, Susan; Laureno, Henry Mar (JPAIR Multidisciplinary Research, 2017)
Educational broadcasting serves as a way to enrich learning. It features programs which aim to reinforce learning and are usually entertaining as well as educational. The study aimed to investigate the needs of the Institute’s adopted local community - Canipaan residents in enhancing learning particularly on livelihood projects through educational broadcast programs. Supported by an interview, this descriptive study was conducted to the residents from the aforementioned institute’s adopted community using percentage equivalent and Pearson r as statistical tools. On relationship between profiles and media resources and its program stations, most of the residents’ profiles such as age, sex, educational attainment, family income and membership in organizations were significantly associated with broadcast resources at 0.01 levels. They were as well associated strongly with TV stations. Meanwhile, regarding the media programs tuned in by these residents through radio and television broadcast firms, majority of them had nothing to tune in as they had no media resources. However, if they would be informed how it would be necessary to be updated especially on current news, health tips and livelihood programs, they would probably switch their interest in listening to educational programs to help improve their lifestyles. Respondents, in general, indicated that they looked forward to an establishment of a community radio station to be able to reach out to their needs.